2018
DOI: 10.1002/ca.23080
|View full text |Cite
|
Sign up to set email alerts
|

Internal and external morphology of mandibular molars: An original micro‐CT study and meta‐analysis with review of implications for endodontic therapy

Abstract: The aim of this radiological micro-CT study and meta-analysis was to determine the morphological features of the root canal anatomy of the mandibular molars. The radiological study included micro-CT scans of 108 mandibular first, 120 mandibular second, and 146 mandibular third molars. For our meta-analysis, an extensive search was conducted through PubMed, Embase, and Web of Science to identify articles eligible for inclusion. Data extracted included investigative method (cadaveric, intraoperative, or imaging)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 97 publications
2
19
0
4
Order By: Relevance
“…The results obtained in this study agree with those observed in Brazilian, Palestinian, Turkish and Chinese populations, where it was seen that the most frequent morphology for mandibular molars is two canals in the mesial root and one in the distal evaluated by CBCT [5,6,24]. The same results were reported in Egyptian and Brazilian populations using micro-CT [9,23] and in a systematic review that included 64 studies using micro-CT [18]. Evidence shows that ethnicity is more related to the number of roots than to the number or distribution of root canals [7], which would explain the similarity with the results obtained in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results obtained in this study agree with those observed in Brazilian, Palestinian, Turkish and Chinese populations, where it was seen that the most frequent morphology for mandibular molars is two canals in the mesial root and one in the distal evaluated by CBCT [5,6,24]. The same results were reported in Egyptian and Brazilian populations using micro-CT [9,23] and in a systematic review that included 64 studies using micro-CT [18]. Evidence shows that ethnicity is more related to the number of roots than to the number or distribution of root canals [7], which would explain the similarity with the results obtained in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The different anatomical variations represent a technical challenge to achieve success in endodontic treatment [5]. Images obtained by CBCT are a reliable tool for the detection and later instrumentation of complex canal configurations [18] and one of the reasons for which their application in endodontics has increased in recent years [17].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed no statistical differences when the volumes obtained by the "visual micro-CT" and the gold standard were compared. Thus, for micro-CT images, both segmentation methods are reliable to calculate root canal volume, corroborating a previous study 11 . Such findings may be attributed to the high resolution and low noise produced by micro-CT, what makes identification of dentin borders accurate.…”
Section: Discussionsupporting
confidence: 89%
“…Certain factors however, such as voxel size, acquisition parameters, and number of acquired images, can directly influence the quality of the produced tomographic images 7 . On the other hand, micro-CT has been recently suggested as a possible gold standard for a precise and non-destructive in vitro study of the 3D anatomy of the root canal system 8,9 due to its high resolution, low noise and precise three-dimensional reproduction of the internal and external morphology of the tooth 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…If the donor tooth is easily accessible, it is possible to treat the root canal before its atraumatic extraction [4,104]. Third molars often present anomalies in the conformation of the roots and root canals, making endodontic treatment difficult [105][106][107]. In these cases, the apical resection of the tooth to be transplanted allows the removal of the more complex part of the root and limits the possible complications of a future orthograde treatment [29].…”
Section: Endodontic Treatmentmentioning
confidence: 99%